2016
DOI: 10.1097/igc.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Staging Lymphadenectomy in Patients With Clear Cell Carcinoma of the Ovary

Abstract: Objective The purpose of this study was to assess the rate of lymph node (LN) metastasis in comprehensively staged ovarian clear cell carcinoma (OCCC) clinically confined to the ovary and determine factors associated with LN metastasis. Methods We identified all cases of OCCC treated at four institutions from January 1994 through December 2011. We included cases with disease grossly confined to the ovary that had surgical staging performed, including at least 10 LNs sampled. Clinical and pathologic data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Third, eligible subjects were OCCC grossly confined to the ovary in another negative study [ 15 ]; a major problem of this study might have been its low rate of LNM (7.1% [10/134]). LNM rate in stage I OCCC is 4%–10% [ 16 18 19 ], which is lower than that in ovarian serous adenocarcinoma [ 20 ], and might be too low to detect a survival benefit for lymphadenectomy statistically. We do not intend to raise an objection to results of previous negative study for therapeutic efficacy of lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, eligible subjects were OCCC grossly confined to the ovary in another negative study [ 15 ]; a major problem of this study might have been its low rate of LNM (7.1% [10/134]). LNM rate in stage I OCCC is 4%–10% [ 16 18 19 ], which is lower than that in ovarian serous adenocarcinoma [ 20 ], and might be too low to detect a survival benefit for lymphadenectomy statistically. We do not intend to raise an objection to results of previous negative study for therapeutic efficacy of lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely to be found at an early-stage and its prognosis is relatively good, while advanced-stage disease has notoriously poor prognosis due to its chemo-resistant characteristics. Opinions vary regarding the therapeutic significance of systematic lymphadenectomy in OCCC [ 14 15 16 17 18 19 20 ]. Despite some negative reports on its therapeutic significance [ 14 15 ], recent retrospective studies showed a potential survival benefit of more extensive lymphadenectomy in OCCC [ 16 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was in line with a previous study, showing that 4.4% to 7.4% of all clinically apparent stage I diseases had metastasis to lymph nodes; with positive cytology or ovarian surface involvement, this rate was as high as 37.5%. [30] This may influence clinical decision-making on whether to perform lymphadenectomy in patients with incidental OCCC found after salpingo-oophorectomy. The question remains as to whether a nodal metastasis rate of approximately 5% is clinically relevant given that adjuvant chemotherapy is recommended even for stage IA OCCC by current treatment guidelines for EOC.…”
Section: Discussionmentioning
confidence: 99%
“…In Mueller's study, 4.4% to 20% of clinically apparent stage I OCCC had lymph node involved. And this rate will be higher with positive cytology or ovarian surface involvement, accounting for as much as 37.5% of metastases 108 . Patients with localized relapse of OCCC tended to have a favorable prognosis (PFS=19 months, PRS=43 months).…”
Section: Metastasismentioning
confidence: 99%
“…Parenchymal organ metastases were occasional in the liver (4% to 5%), lungs (3.3% to 9.5%) and spleen (1.6%), respectively 15 , 105 , 108 , 109 . The liver and lung are commonly affected organs, similar to HGSC.…”
Section: Metastasismentioning
confidence: 99%